The war from “A” to “Z” – a particular interpretation of Os Cus de Judas, de António Lobo Antunes. - Niza Silva, Alba Valéria (2017)
In this paper, the novel "Os cus de Judas", by António Lobo Antunes, is analyzed with focus on the narrative structure, on some themes related to memories and on language. The book is examined according to Nietzsche´s theory about language and truth and according to a theory formulated by Blanchot in his study about the "experience of the outside".